Análisis del uso de la mecanización agrícola en el Ecuador - Yela Cervantes, Andrea Anahy (2021)
Among the countless activities in the agricultural sector, properly performed mechanized operations significantly help the producer, allowing him to make better use of resources with less effort in the tasks that range from soil preparation to final product transportation. These tasks require human resources, which is why the use of agricultural machinery is necessary. However, in Ecuador, incorporating agricultural machinery basically depends on production system, size of the agricultural production unit (APUs), producer’s socioeconomic situation and topographic conditions. The present study aimed to determine the impact of agricultural mechanization on the development of agricultural production in the country. Most mechanization measures in agriculture are produced for reasons of economy at work: increasing labor productivity (yield per worker) and making work physically easier and less exhausting for the farmer. To achieve sustainable food security, in relation to the identified factors, the necessary recommendations and government support policies in the agricultural sector are imperative from the point of view of increasing mechanization coverage.